Efeito da largura de pulso de corrente na oxidação por plasma eletrolítico em alumínio comercial puro - Lima, Richelly Nayhene de (2020)
Plasma electrolytic oxidation (PEO) is a technique used to obtain ceramic coatings on light metal surfaces, such as magnesium, titanium and aluminum. Up to now, the PEO process has been performed either by direct current or by low frequency pulsed current ( 1 kHz) current pulse width on microdischarge characteristics and morphology, phase composition and the thermal and corrosive behavior of PEO coatings obtained on pure commercial aluminum (AA1050). was studied. The PEO treatment was performed in an electrolyte cell containing Na2SiO3 (2 g.L-1 ) as an electrolyte solution. The physical and chemical characterization of the coatings was made using the techniques of scanning electron microscopy (SEM), X-ray dispersive energy spectrometry (EDS) and X-ray diffraction (XRD) using Bragg Brentano and Seeman Bohlin configuration. To evaluate the optical properties, the optical reflectance technique in the UV-Vis-NIR range was used. Electrochemical corrosion tests were performed by linear potentiodynamic polarization (LPP) and by electrochemical impedance spectroscopy (EIE). It was observed that the lower the ton, the less intense and more distributed the discharges are, which led to an increase in porosity and a decrease in thickness. The XRD analyzes showed that when ton increase, the presence of α-Al2O3 phase is verified in the inner layer, γ-Al2O3 phase on the surface and SiO2 phase at the edges of the pores or near cracks. Regarding the optical behavior, PEO coatings showed absorbance properties superior to aluminum in the solar spectrum, obtaining a thermal efficiency of 62% in a water heating system. The electrochemical corrosion tests showed that the increase in ton provided a decrease in corrosion kinetics and an increase in corrosion resistance in 3.5% NaCl medium. In summary, the pulses of 100 and 150 µs provided the best conditions for obtaining optical trap surfaces with good resistance to corrosion due to their morphologies and chemical composition.